Influencing Factors Profitability of Manufacturing Companies on Indonesia Stock Exchange - Hety Devita*; Nerissa Arviana (Universitas Syiah Kuala, 2023)
The achievement of the company's goals is to increase profitability, namelyThe company's ability to obtain sales profits, total assets and own capitalResearch Objectives To find out Current Ratios, Company Size, Age of influential companies on Return On Assets in companies listed on the IDX. Population from this research is the company's fundamental report on the IDX for 6 years from 2017-2022. Based on the criteria in the picking The sample was obtained as a total of 6 companies from 36 sub companies consumer sector listed on the Indonesia Stock Exchange for the period 2017-2022, The results showed that the current ratio, company size had a positive effect on profitability and the age of the company negatively affected the profitability of manufacturing companies